(untitled) (Ameghiniana, 2009)
Roca Formation is a stratigraphic succession of marine and continental sediments that belongs to Malargüe Group, which was deposited from the Late Campanian to the Danian in the Neuquén Basin, western Argentina. Fossil vertebrates recovered at different outcroppings of this lithostratigraphic unit correspond to marine taxa. The turtle material studied here was collected from the lower section of Roca Formation (Maastrichtian?-Danian) in northeastern Lago Pelegrini (38º 40’ 06’’S, 67º 52’ 02’’ O), Rio Negro Province. Remains of carapace and plastron of continental turtles were assigned to indeterminate chelid pleurodires and to Yaminuechelys cf. maior (Staesche, 1929). This record of chelid turtles in Roca Formation confirms the existence of marine paleoenvironments with continental influence and represents the first record of Danian continental vertebrates in the Neuquén Basin.